No payment guarantees for agri-environment schemes (Arable farming, 2006)
The uncertainty will not stop Natural England issuing new agreements for Entry Level Stewardship (ELS) after January 1, 2007. However, agreements will be subject to delays. They will also be provisional, dependent on the UK's RDP receiving EU approval, which is unlikely to be before autumn 2007.